Komunikasi Antar Pribadi Antara Reseller dengan Produsen Cantiqa Kemiri - Rubyanata Harahap; Wulan Tri Gartanti; Dadi Ahmadi (Inter Komunika, 2018)
Abstract. Interpersonal communication among business people is very interesting because every individual in each generation will be different in how to communicate. In business cooperation between producers and product resellers, the means of conveying the intent in the expressed communication message will differ depending on the purpose of the message delivery and the purpose of the contents of the message itself. So that the influence between the communication intentions conveyed will encourage the communicator to be able to provide added value.Communication is the sending of a message from someone and is received by another person with immediate effects and feedback, so that not only aims to build effective communication in interpersonal communication but also wants to create an effect. In relation to interpersonal communication, res-sellers and producers carry out communication with the aim of creating effective communication in order to carry out good cooperation. This study examines interpersonal communication between Cantiqa Kemiri producers and resellers. This research uses descriptive method with data collection techniques through interviews, literature studies, and observations. Key informants in this study were Cantiqa Kemiri producers and resellers. The results of this study indicate that interpersonal communication between Cantiqa Kemiri producers and resellers involves several aspects such as openness, empathy, support, positive feelings, and equality in maintaining relationships between each other so that product sales remain optimal.Keywords: Communication, Interpersonal Communication, Cooperation, Business, Manufacturer, ResellerAbstrak. Komunikasi antarpribadi diantara para pelaku bisnis menjadi sangat menarik diperhatikan karena setiap individu dalam setiap generasi akan berbeda cara berkomunikasinya. Dalam kerjasama bisnis diantara produsen dan reseller produk, cara penyampaian maksud dalam pesan komunikasi yang diutarakan akan berbeda tergantung dari tujuan penyampaian pesan serta maksud dari isi pesan itu sendiri. Sehingga pengaruh diantara maksud komunikasi yang disampaikan akan mendorong pelaku komunikasi tersebut untuk bias memberikan nilai tambah. Komunikasi merupakan pengiriman pesan dari seseorang dan diterima oleh orang lain dengan efek dan umpan balik yang langsung, sehingga bukan hanya bertujuan membangun komunikasi yang efektif dalam komunikasi antarpribadi tetapi juga ingin menciptakan efek. Dalam kaitannya dengan komunikasi antarpribadi, reseller dan produsen menjalankan komunikasi dengan tujuan untuk menciptakan komunikasi yang efektif agar dapat melaksanakan kerjasama yang baik. Penelitian ini meneliti mengenai komunikasi antarpribadi antara produsen dan reseller Cantiqa Kemiri. Penelitian ini menggunakan metode deskriptif dengan teknik pengumpulan data melalui wawancara, studi kepustakaan, dan observasi. Key informan dalam penelitian ini adalah produsen dan reseller Cantiqa Kemiri. Hasil dari penelitian ini menunjukan bahwa komunikasi antarpribadi antara produsen dan reseller Cantiqa Kemiri melibatkan beberapa aspek seperti keterbukaan, empati, dukungan, rasa positif, dan kesetaraan dalam menjaga hubungan antara satu sama lain sehingga penjualan produk tetap optimal.Kata Kunci: Komunikasi, KomunikasiAntarpribadi, Kerjasama, Bisnis, Produsen, Reseller